Wearable Prophylaxis Tool for AI-Driven Identification of Early Warning Patterns of Pressure Ulcers - Gruenerbel, Lorenz; Heinrich, Ferdinand; Böhlhoff-Martin, Jonathan; Röper, Lynn; Machens, Hans Günther; Gruenerbel, Arthur; Schillinger, Moritz; Kist, Andreas; Wenninger, Franz; Richter, Martin; Steinbacher, Leonard (Bioengineering, 2023)
As today’s society ages, age-related diseases become more frequent. One very common but yet preventable disease is the development of pressure ulcers (PUs). PUs can occur if tissue is exposed to a long-lasting pressure load, e.g., lying on tissue without turning. The cure of PUs requires intensive care, especially for the elderly or people with preexisting conditions whose tissue needs longer healing times. The consequences are heavy suffering for the patient and extreme costs for the health care system. To avoid these consequences, our objective is to develop a pressure ulcer prophylaxis device. For that, we built a new sensor system able to monitor the pressure load and tissue vital signs in immediate local proximity at patient’s predilection sites. In the clinical study, we found several indicators showing correlations between tissue perfusion and the risk of PU development, including strongly reduced SpO (Formula presented.) levels in body tissue prior to a diagnosed PU. Finally, we propose a prophylaxis system that allows for the prediction of PU developments in early stages before they become visible. This work is the first step in generating an effective system to warn patients or caregivers about developing PUs and taking appropriate preventative measures. Widespread application could reduce patient suffering and lead to substantial cost savings.
Created from Fastlane, Scopus look-up
Keywords: AI; bedsore; continuous monitoring; decubitus; digital health; foot ulcer; machine learning; personalized medicine; pressure ulcers; prevention